Comparison of combined disc synergy test and double disc synergy test for phenotypic detection of metallo-ß-lactamase among the clinical isolates of gram-negative bacilli - Chowdhury, Rifat Asma; Sharmin, Sabrina; Karim Chowdhury, Abu Hena M. Saiful; Akter, Nasima; Ahmed, Shakeel; Choudhury, Gulshan Nigar (International Journal of Research in Medical Sciences, 2022)
Background: Metallo-β-lactamases (MBL) have a wide spectrum of activity and they confer a higher level of resistance to all β-lactams antibiotics including Carbapenem. The active site in MBLs contains either 1 or 2 Zn2+ ions for their catalytic mechanism. All MBLs share a common feature of being inhibited by EDTA. Metallo-β-lactamase-producing gram-negative bacteria are the most important nosocomial pathogens. The present study was conducted to detect Metallo-β-lactamase (MBL) production in gram-negative bacilli by Combined Disc Synergy Test (CDST) and Double Disc Synergy Test (DDST) with 0.1M EDTA as a chelator and to see their antibiotic susceptibility pattern of them. Methods: The cross-sectional observational study was carried out in the Department of Microbiology, Chittagong Medical College, during the period of July 2015 to June 2016. Samples were collected from patients admitted to CMCH. Standard Microbiological procedures and biochemical tests were carried out for the isolation and identification of MBL. SPSS software is used for data analysis. Results: When 66 screening positive MBL isolates were subjected to the phenotypic confirmatory test CDST detected 50 (25.4%) and DDST detected 48 (24.4%) as MBL producers. Among these isolates, we found Acinetobacter spp. 7 (100%), as the leading MBL producer followed by Pseudomonas spp. 16 (32.6%), E. coli 10 (20%) and Klebsiella spp. 15 (17.4%). Conclusions: In a laboratory where multiplex PCR molecular set-up is not available CDST and DDST are convenient phenotypic methods and can be implemented in routine microbiological laboratories as well as in primary health care setup for daily application to monitor the production of MBLs.